Effect of Fertilization, Cultivar and Weeds on the Productive Behavior of Tall Fescue (Lolium arundinaceum (Schreb.) Darbysh) - Heguy, Barbara (2024)
The agricultural intensification in Argentina's Pampean region has pushed livestock farming towards marginal areas such as the Salado Depression. In this context, tall fescue pastures emerge as a sustainable forage alternative. However, their production can be limited by factors such as soil fertility and weed competition. This study evaluates the impact of fertilization and weed presence on the yield of five tall fescue cultivars during their first year of establishment in the Salado Depression. The experiment was conducted in a pasture of a farm located in the district of Punta Indio, in the province of Buenos Aires, Argentina. A completely randomized block design was implemented with ten treatments and three replications, where the factors were five cultivars with and without fertilization at sowing (60 kg ha⁻¹ of diammonium phosphate). Biomass cuts were taken in September and December, and tiller density and weight were counted. The results showed that fertilization at sowing significantly increased biomass production, mainly due to an increase in tiller density. On the other hand, competition with other annual grasses reduced biomass production, especially in unfertilized treatments. Although the evaluated cultivars responded similarly to the treatments, differences in tiller density were observed over time, highlighting the importance of selecting cultivars adapted to local conditions. Fertilization at the time of sowing is confirmed as a key practice to improve the yield of tall fescue pastures in the Salado Depression. However, an integrated management that combines the selection of suitable cultivars and weed control is essential to achieve maximum productive potential, pasture permanence, and ensure the sustainability of these grazing systems.